Intra-Arterial Chemotherapy as Primary Therapy for Retinoblastoma in Infants Less than 3 Months of Age: A Series of 10 Case-Studies - Chen, Miaojuan; Zhao, Junyang; Xia, Jiejun; Liu, Zhenyin; Jiang, Hua; Shen, Gang; Li, Haibo; Jiang, Yizhou; Zhang, Jing (PLOS ONE, 2016)
Purpose Retinoblastoma is the most common primary malignant intra-ocular tumor in children. Although intra-arterial chemotherapy (IAC) by selectively infusing chemotherapy through the ophthalmic artery has become an essential technique in the treatment of advanced intra-ocular retinoblastoma in children, the outcome of IAC as primary therapy for infants less than 3 months of age remains unknown. In this retrospective study, we reviewed the outcome of IAC as primary therapy for retinoblastoma in infants less than 3 months of age. Methods We retrospectively reviewed ten retinoblastoma patients attending our center from January 2009 to September 2015 and beginning primary IAC before the age of 3 months. The patient characteristics, overall outcomes and therapy-related complications were assessed. Results The mean patient age at the first IAC treatment was 10.4 weeks (range 4.9–12.9 weeks). These eyes were classified according to the International Classification of Retinoblastoma (ICRB) as group A (n = 0), B (n = 2), C (n = 0), D (n = 9), or E (n = 2). A total of 28 catheterizations were performed, and the procedure was stopped in one patient because of internal carotid artery spasm. Each eye received a mean of 2.6 cycles of IAC (range 2–4 cycles). After IAC with a mean follow-up of 28.3 months (range 9–65 months), tumor regression was observed in 12 of 13 eyes. One eye was enucleated due to tumor progression. All patients are alive and no patient has developed metastatic disease or other malignancies. Conclusions Our experience suggests IAC as primary therapy is a feasible and promising treatment for retinoblastoma in infants less than 3 months of age.